Nobiletin mitigates benign prostatic hyperplasia by suppressing prostate cell proliferation through regulation of cell cycle progression, signaling pathways, transcription factor activity, and the androgen-signaling axis - Song, Jun-Hui; Lee, Daeun; Hwang, Byungdoo; Hwang, Seon-Kyung; Choo, Sumin; Jeong, Hyeon Ji; Kim, Hoon; Cha, Byungyoon; Yun, Seok-Joong; Choi, Yung Hyun; Kim, Wun-Jae; Moon, Sung-Kwon (Frontiers in Pharmacology, 2025)
Background and aimBenign prostatic hyperplasia (BPH) involves androgen-driven proliferation with reduced apoptosis. Current 5α-reductase inhibitors can cause adverse effects, motivating safer options. We evaluated whether nobiletin, a polymethoxyflavonoid, mitigates BPH features.MethodologyIn vitro, nobiletin was applied to BPH-1 epithelial and WPMY-1 stromal cells to assess anti-proliferative effects. In vivo efficacy was tested in a testosterone-induced BPH rat model administered oral nobiletin (1 or 5 mg/kg).ResultsNobiletin induced G0/G1 phase cell cycle arrest by suppressing cyclin D1, cyclin E, and cyclin-dependent kinase 2 (CDK2), while elevating p21 and p27 expression. Expression of 5α-reductase, androgen receptor (AR), fibroblast growth factor (FGF), epidermal growth factor (EGF), and B-cell lymphoma 2 (Bcl-2) was reduced, whereas Bcl-2–associated X protein (Bax) was increased. Nobiletin modulated phosphorylation of c-Jun N-terminal kinase (JNK) and p38 and suppression of protein kinase B (AKT) phosphorylation. Nobiletin reduced nuclear factor kappa B (NF-κB) DNA-binding activity, which was dependent on JNK and p38. In vivo, nobiletin reduced prostate size, weight, and epithelial thickness, accompanied by molecular markers changing in the same direction as in vitro. Molecular docking analysis further supported the potential of nobiletin to bind 5α-reductase type 2 at the catalytic site.ConclusionThese results highlight the potential of nobiletin as a novel therapeutic option for BPH.